(NHC-olefin)-nickel(0) nanoparticles: an efficient and selective catalyst for hydrogenation reactions at low temperature and pressure - Avello, Marta G.; Singh, Geetika; Truong-Phuoc, Lai; Vidal, Loic; Papaefthimiou, Vasiliki; Chesse, Matthieu; Gruber, Nathalie; Chetcuti, Michael J.; Vanka, Kumar; Ritleng, Vincent; Pham-Huu, Cuong; Michon, Christophe (Journal of Catalysis, 2026)
The reduction of a NHC-cinnamyl nickel(II) organometallic complex through the use of different MeMgBr or MeMgCl reagents led to two types of NHC-olefin-coordinated nickel nanoparticles. Both of these unsupported nickel-NHC based nanomaterials behaved under hydrogen pressure as effective and selective catalysts operating at low temperature (<= 80 degrees C), pressure (<= 20 bar) and loading (<= 6 mol%) for the reductions of broad scopes of alkenes, alkynes, imines and heterocycles, including a challenging tetra-substituted alkene. Among these two nickel-NHC nanocatalysts, the one generated with MeMgCl showed a significant high catalytic activity with high yields and could stand the comparison with Raney nickel and state-of-the-art nickel nanocatalysts. For example, by studying the hydrogenation of 1-phenylcyclohexene in ethanol at 60 degrees C under 10 bar of H2, 3 mol% of this catalyst achieved the reaction within a single hour on a 5 mmol/0.8 g substrate scale with a yield of 96 %, a turnover number (TON) of 32 and a turnover frequency (TOF) of 32. Characterizations confirmed the coordination of the NHC-olefin ligands to the nickel nanoparticles, the reduced state of the nickel and the (poly-) crystallinity of the nanoparticles.
Keywords: alkenes; Alkynes; heterocycles; Hydrogenation; imines; N -heterocyclic carbene ligand; nanocatalysis; Nickel